Assessing the Effect of Compensation Packages, Work-Life Balance Policies, and Career Development Opportunities on Employee Retention: A Case Study of MSME Employee - Suprayitno, Degdo (International Journal of Business, Law, and Education, 2024)
In today's competitive business environment, Micro, Small, and Medium Enterprises (MSMEs) face significant challenges in attracting and retaining top talent. This study examines the impact of compensation packages, work-life balance policies, and career development opportunities on employee retention within MSMEs. Using a quantitative research design and Partial Least Squares Structural Equation Modeling (PLS-SEM), data from 300 respondents were analyzed to explore the relationships between these factors. The findings reveal significant positive relationships between compensation packages, work-life balance policies, career development opportunities, and employee retention. These results highlight the importance of strategic investments in human capital and the creation of conducive work environments to foster employee loyalty and commitment within MSMEs.